1999
DOI: 10.1097/00005373-199912000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Renal Venous Pressure on Renal Function

Abstract: Elevated RVP alone leads to decreased renal artery blood flow and glomerular filtration rate and increased plasma renin activity, serum aldosterone, and urinary protein leak. These changes are consistent with the renal pathophysiology seen in AACS, morbid obesity, and preeclampsia. The changes are partially or completely reversed by decreasing renal venous pressure as occurs with abdominal decompression for AACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(96 citation statements)
references
References 13 publications
4
88
0
4
Order By: Relevance
“…Our results are in line with the previous literature reporting renal [19][20][21][22] and hepatic [21] dysfunction (Tables 1, 2, Figs 1, 2). Toens et al [23] used a porcine model with IAP ~30 mm Hg for 24 h, induced by CO 2 insufflation, and observed necrosis in the central vein of the liver, as well as tubular and glomerular necrosis.…”
Section: Impact Of Intra-abdominal Hypertension On the Liver Kidneyssupporting
confidence: 93%
“…Our results are in line with the previous literature reporting renal [19][20][21][22] and hepatic [21] dysfunction (Tables 1, 2, Figs 1, 2). Toens et al [23] used a porcine model with IAP ~30 mm Hg for 24 h, induced by CO 2 insufflation, and observed necrosis in the central vein of the liver, as well as tubular and glomerular necrosis.…”
Section: Impact Of Intra-abdominal Hypertension On the Liver Kidneyssupporting
confidence: 93%
“…Increased intra-abdominal pressure from visceral fat, a common occurrence in morbidly obese individuals (140 -142), may cause renal vein compression and may therefore raise renal venous pressure and diminish renal perfusion (143). In addition, raised intra-abdominal pressure may cause increased inferior vena cava pressure, and this may impair venous outflow from the renal veins (144).…”
Section: Other Potential Hemodynamic Factorsmentioning
confidence: 99%
“…It indicated that the high renin activity was corrected with NCP. Some investigators have suggested that elevated renal pressures (venous and interstitial) reduce glomerular filtration, affect intrarenal blood flow, and stimulate release of renin [11]. With reduced glomerular filtration, there is reduction of sodium delivery to the macula densa, which triggers renin secretion from the juxtaglomerular cells.…”
Section: Discussionmentioning
confidence: 99%